(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2019)
This paper examines the factors that sparked tensions between the Malays and the Chinese after the Japanese military rule in Malaya. The Pangkor Treaty of 1874 had changed the British colonial landscape in Malaya. Imperialism and colonialism led to the influx of immigrants in Malaya and the loss of the rights of the Malays in their own homeland. The Japanese military rule gave opportunity to the communists to commit atrocities, especially when legitimising their power. This sowed the seeds of prejudice which then resulted in Malay-Chinese racial conflict in Malaya. The Malays, who had been ill-treated by the colonialists, began to think about the nation’s survival. The present research employed a historical approach methodology, colonial records and interviews with local informants to study existing problems. It shows that Malay-Chinese conflict raised nationalistic feelings among the Malays to stand up against their colonizers. Keywords: Pangkor Treaty, imperialism and colonialism, Japan, Malay-Chinese conflict, nationalism